2022
DOI: 10.1111/jon.12989
|View full text |Cite
|
Sign up to set email alerts
|

Echoencephalography of encephalopathy due to congenital lymphocytic choriomeningitis virus

Abstract: Congenital lymphocytic choriomeningitis virus (LCMV) infection is a transient intrauterine viral infection with selective teratogenicity depending on the timing of the primary maternal infection. LCMV is cleared from the body of the fetus after the acute phase of illness and, in most cases, has lost its virulence at the time of birth. LCMV competes with extracellular matrix proteins for its tropism toward heavily glycosylated alpha-dystroglycan. In the first trimester, while tropism toward heart myoblasts is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…They also noted that PMG is a group of disorders that spares the cerebellar cortex in most cases 13 . Cortical cerebellar dysplasia in association with PMG has been reported in intrauterine cytomegalovirus (CMV), Zika, or lymphocytic choriomeningitis virus (LCMV) infections 35,36 . PMG with cerebellar dysplasia can occur in metabolic disorders, such as peroxisomal disorders, 37 and can be also a feature of some tubulinopathies 38,39 and ciliopathies 40,41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also noted that PMG is a group of disorders that spares the cerebellar cortex in most cases 13 . Cortical cerebellar dysplasia in association with PMG has been reported in intrauterine cytomegalovirus (CMV), Zika, or lymphocytic choriomeningitis virus (LCMV) infections 35,36 . PMG with cerebellar dysplasia can occur in metabolic disorders, such as peroxisomal disorders, 37 and can be also a feature of some tubulinopathies 38,39 and ciliopathies 40,41 …”
Section: Discussionmentioning
confidence: 99%
“…13 Cortical cerebellar dysplasia in association with PMG has been reported in intrauterine cytomegalovirus (CMV), Zika, or lymphocytic choriomeningitis virus (LCMV) infections. 35,36 PMG with cerebellar dysplasia can occur in metabolic disorders, such as peroxisomal disorders, 37 and can be also a feature of some tubulinopathies 38,39 and ciliopathies. 40,41 Because of the similarity of the brain pathology in patients with ADGRG1/GPR56 mutations with that reported in CMD, the original term BFPP is better replaced by a more appropriate one, such as "cobblestone/polymicrogyria-like cortical dysplasia" in order to pool together this spectrum of anomalies seen in both disorders.…”
Section: F I G U R E 5 Cerebellar Histological Hematoxylin-eosin Stai...mentioning
confidence: 99%
“…Once LCMV infection of the CNS occurs, cells such as neurons and astrocytes are affected [222]. On the other hand, when a woman acquires LCMV infection during the second trimester of pregnancy, it has been observed that this infection can lead to the development of congenital disabilities in the fetus [110,111]. These defects may include hydrocephalus and chorioretinitis (Figure 1B) (Table 1) [110].…”
Section: Lymphocytic Choriomeningitis Virusmentioning
confidence: 99%